Anatomy, taxonomy, ontogeny and phylogeny of basal mosasaurians (Squamata, Mosasauria) and their implications to the evolution of Anguimorpha - Augusta, Bruno Gonçalves (2019)
Mosasauria is a clade of essentially Late Cretaceous marine reptiles. Although well known by several nicely preserved specimens, phylogenetic relationships of mosasaurians within Squamata are still a matter of intense debate. Most of the works discussing the relationships of mosasaurians in global contexts of squamates were based mainly on more derived taxa, including only few basal forms. Here the anatomy, phylogeny, ontogeny and taxonomy of the basalmost mosasaurian radiation, the commonly known \"dolichosaurs\", is reviewed, mostly on the light of new and exquisitely preserved coniasaur remains from Texas. New remains described here encompass dozens of specimens, including a new species represented by a gravid female and several embryos. A revision of the genus Coniasaurus suggest it as encompassing four species: C. crassidens, C. longicollis (former Dolichosaurus longicollis), C. gracilodens and the new taxon described here. Contrary to what is observed in more derived forms, the patterns of tooth attachment in coniasaurs are very similar to those of varanoids, suggesting similarities between tooth attachment and implantation in snakes and derived mosasaurs to be the result of homoplasies. The evolution of the dolichosaurian postcranial anatomy is assessed, finding new diagnostic characters for several distinct lineages. A phylogenetic analysis of Mosasauria in a global matrix of squamates, including the largest sample of basal forms ever tested, consistently found the group to be closely related to Varanoidea, rejecting the hypotheses of the group being closely related either to snakes or lying in a more basal position among squamates. Results gathered by this thesis are expected to greatly contribute to the knowledge of this astonishing group